The effects of wide range of compositional changes on the martensitic transformation characteristics of NiTiHf shape memory alloys. (1st March 2019) - Umale, Tejas; Salas, Daniel; Tomes, Bradley; Arroyave, Raymundo; Karaman, Ibrahim
Abstract: The effects of composition on the martensitic transformation characteristics of NiTiHf shape memory alloys are systematically explored. Transformation temperatures (TTs) demonstrate a non-monotonic dependence on Ni and Hf concentrations. For Ni > 50 at%, TTs decrease with small Hf additions, attain a minimum or are completely suppressed, depending on Ni content, followed by a significant increase with Hf content. This initial drop in TTs becomes more pronounced with higher Ni contents and is attributed to the increase in nickel anti-site defects along with bulky substitutional Hf contributing to the increase in local lattice distortions along with the re-distribution of Ti and Hf. Graphical abstract: